Effect of alcohols and enhancers on permeation enhancement of ketorolac - Chandra, Amrish; Sharma, Pramod Kumar; Irchhiaya, Raghuveer (Asian Journal of Pharmaceutics (AJP), 2014)
A reservoir-type transdermal patch for the delivery of ketorolac was studied. The low permeability of the skin is the rate-limiting step for delivery of most of the drugs. Studies were carried out to investigate the effect of pH, alcohols, and chemical permeation enhancers on the in vitro permeation of ketorolac. The reservoir core of the transdermal patch was filled with the hydrogel of a nonionic polymer, methocel K15M (hydroxyl propyl methylcellulose, HPMC) formulated at an optimized pH of 5.4. Enhanced in vitro permeation was achieved after the incorporation of the alcohols. Higher enhancement was produced by short-chain alcohols like ethanol and isopropyl alcohol (IPA). Propylene glycol (PG) along with other alcohols, viz. n-propanol, n-butanol, and n-pentanol, lagged behind. An exponential rise in permeation was observed in flux with an increase in the concentration of IPA. At 25% w/w IPA concentration, the observed ketorolac flux was 18.04 mg/cm2/h. Terpene containing eucalyptus oil was studied to determine its permeation enhancement capability. The increase in the concentration of eucalyptus oil enhanced the drug permeation and a maximum flux of 66.38 and 90.56 mg/cm2/h was achieved at 10 and 15% w/w concentrations. The anti-inflammatory potential of the transdermal formulation was evaluated on a carrageenan-induced paw edema model, with 41.67% inhibition at 6 h. The skin irritation potential was evaluated by the Drazie test and the formulations prepared were found to be safe. The reservoir-type transdermal patch for the delivery of ketorolac appeared to be feasible for delivering ketorolac across the skin.